Relación entre el motivo de consulta ortodóncico, el diagnóstico clínico de la maloclusión y el grado de satisfacción postratamiento* parte II: grado de satisfacción - Mejía-Villa, Raúl; Flórez-Tobón, Claudia María; Vargas-Zabala, Clara Patricia (Revista Facultad de Odontología Universidad de Antioquia, 2017)
The purpose of this study was to determine the orthodontics posttreatment satisfaction level, and its determinants factors in 250 patients that had orthodontics treatment in four dental centers in the city of Medellin. The information was gathered by a survey, and for its analysis, it was applied the simple or correct( –I 71- square" (A2) test. The results show that 94.4% of the patients were satisfied with the results of the orthodontics treatment; the posttreatment satisfaction level has a multifactorial source; so for the "regularly satisfied", and "unsatisfied" patients, exists multiples causes of unsatisfaction. The "solution of the initial reasons of the patients consultation", was one of the factors most determinant by the satisfaction level in the patients to whom it was completely solved, but the difference of satisfaction between them, and those patients to whom the initial reason of consultation only was partially solved, it reaches a statistical level of significance of 0%.